An evaluation of the use of caries risk/susceptibility assessment in an undergraduate dental curriculum - Nasseripour, Melanie; Hasan, Adam; Chapple, Liz; Chopra, Anusha; Cracknell, Lucy; Maiter, Zahraa; Banerjee, Aviijit (Frontiers in Oral Health, 2024)
There has been a paradigm shift in patient care to a minimum intervention oral care approach (MIOC). We must ensure graduating oral healthcare team members are able to provide phased personalised care plans alongside behavioural management support to patients. The purpose of this study was to establish that using an adjunctive Caries Risk/Susceptibility Assessment (CRSA) technology (PreViser), had an impact on the behaviour, perception and knowledge of dental undergraduate students and their clinical teachers, regarding the benefits of such an oral health assessment. We used a mixed methods approach with a convergent parallel design consisting of collecting quantitative data through questionnaires presented to 4 cohorts of year 4 dental students (n=150 per cohort) and their clinical teachers (n=10) and qualitative data from structured interviews with students (n=5) and teachers (n=7) with suitable statistical analysis and interpretation. Results: The statistically significant items showed better behaviour, perception and knowledge toward CRSA of Group C (BDS4-22T1) cohort in comparison to Group A (BDS3-20T2) cohort. Group D (BDS4-22T2) students felt more confident using the PreViser as a CRSA tool. We note that Group C cohort were more likely to carry out a diet analysis for their patients and were less likely to be negatively impacted by time constraints than Group D. Both cohorts were equally confident in using PreViser for CRSA. From a qualitative perspective, although competence and confidence appeared high, students and teachers acknowledged they would need more support to use it chairside. The main barrier listed was that clinical teachers either preferred their own ways of assessing or did not know how to use the tool and therefore did not encourage using it. Those who did use PreViser highlighted that it was straightforward to use and was a systematic approach, enabling communication with the patients. Conclusion: The cumulative benefit of training and use had an impact on the students’ knowledge, competence, confidence about CRSA and made teaching and helping them deliver CRSA easier. The importance of CRSA was felt to be more evident right after training. Further research is required to understand factors influencing student behaviour, perception and knowledge in CRSA.